Advancing the rights of the sexually exploited children in need of protection and rehabilitation within the legislative framework in Malaysia: A socio-legal analysis / Najwa Rosli - Najwa , Rosli (2019)

(untitled)
Every child has the universally recognized right to be protected from any forms of sexual exploitation and sexual abuse by virtue of Article 34 of the UNCRC. The foundational aspect in protecting children against sexual exploitation is the establishment of a legal framework that fulfils international standards. This is crucial to ensure that the national legal framework is effective, as well as to facilitate international collaboration and to curtail forum shopping. Within the Malaysian legal framework, children who are exposed to or involved in sexual exploitation are categorized as ‘children in need of protection and rehabilitation’ under Part VI of the Child Act 2001 (CA 2001). Under the said provision, these children may be placed at the place of refuge as part of the protection procedures. Past research findings exhibit several controversial issues pertaining to the children’s rights at the places of refuge. The findings suggest that, more often than not, the children have not been treated with dignity and respect, inadequate education opportunity, and insufficient moral support. These are against their rights enshrined in the UNCRC. With the intent of advancing the rights of children in need of protection and rehabilitation in Malaysia, this thesis seeks to, (i) evaluate the overall legal framework concerning children in need of protection and rehabilitation in Malaysia particularly as to the extent of compliance to the UNCRC and other ratified international instruments; (ii) to investigate the realities on the implementation of child rights at the places of refuge; and (iii) propose legal and administrative reforms for the purpose of ensuring the fundamental rights of the children in need of protection and rehabilitation are effectively safeguarded. This research has adopted mixed doctrinal and socio-legal approaches. Apart from conducting library research to examine legal literatures, empirical data was also collected to provide insights on the actual application of the law, particularly to assess the implementation of the children rights at the place of refuge. It is submitted that the current Malaysian legal framework largely meets with the international standards. However, there are three pertinent areas that requires attention and improvements, namely; (i) the non-availability of provision on the legal presumption that persons under the age of 18 years who are involved in prostitution shall always be the victims of sexual exploitation, (ii) the inadequacy of provision establishing extra-territorial jurisdiction, and (iii) the restricted access of the child victims to compensation. Furthermore, it is submitted that the children’s rights are reasonably protected and implemented at the places of refuge run by the government. With the adoption of Regulations 2017, MS-ISO 9001: 2008 and Place of Refuge CMS, the measures to safeguard the well-being of the children are standardized in Malaysia. Nevertheless, the research found that the are certain rights and aspect which are less satisfactorily promoted and/ or requires improvements such as the right to freedom of expression, right to family support, right to skill and vocational trainings, and the promotion of self-worthiness and prevention of future sexual abuse or exploitation.